2017
DOI: 10.1007/s00223-017-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Bone Repair with Hydroxyapatite: A Systematic Review

Abstract: The aim of this study was to evaluate the morphological bone response in animal experiments by applying hydroxyapatite grafts in critical and non-critical size bone defects. Current report followed the guidelines established by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Animal experiments were selected by assessing repair of bone defects with hydroxyapatite as bone graft and with blood clot only as control. Eight articles were identified in specialized literature and included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 59 publications
1
47
0
3
Order By: Relevance
“…17,18 CaP based biomaterials and their composites have been extensively employed in various biomedical areas, such as drug delivery, [19][20][21] protein adsorption, 22 bioimaging, 23,24 bone defect repair/tissue engineering. 25,26 For example, CaP coated metallic scaffolds are considered as the promising weight bearing implants owing to their advantages of high biocompatibility and strength. [27][28][29] Meanwhile, in previous studies, the protein drugs of growth factors, such as, morphogenetic protein (BMP), vascular endothelial growth factor (VEGF), basic broblast growth factor (bFGF) and transforming growth factor-beta (TGF-b), were adopted and loaded in CaP materials to prepare biomaterials which are favorable for bone defect repair.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 CaP based biomaterials and their composites have been extensively employed in various biomedical areas, such as drug delivery, [19][20][21] protein adsorption, 22 bioimaging, 23,24 bone defect repair/tissue engineering. 25,26 For example, CaP coated metallic scaffolds are considered as the promising weight bearing implants owing to their advantages of high biocompatibility and strength. [27][28][29] Meanwhile, in previous studies, the protein drugs of growth factors, such as, morphogenetic protein (BMP), vascular endothelial growth factor (VEGF), basic broblast growth factor (bFGF) and transforming growth factor-beta (TGF-b), were adopted and loaded in CaP materials to prepare biomaterials which are favorable for bone defect repair.…”
Section: Introductionmentioning
confidence: 99%
“…Laminin also has several roles in cell migration, survival, attachment, and promotes osteogenic differentiation [ 28 ]. Collagen I, GAG, fibronectin [ 29 ] and HA [ 30 ] also promote the bone repair and remodeling. We showed that the number of osteocytes and bone area increased significantly in the defect treated with DC + HA scaffold compared to the untreated control defect.…”
Section: Discussionmentioning
confidence: 99%
“…Laminin also has several roles in cell migration, survival, attachment, and promotes osteogenic differentiation [28]. Collagen I, GAG, bronectin [29] and HA [30] also promote the bone repair and remodeling. We showed that the number of osteocytes and bone area increased signi cantly in the defect treated with DC+HA scaffold compared to the untreated control defect.…”
Section: Discussionmentioning
confidence: 99%